Die gawe van onderskeiding as spieël vir die kerk - Beyers, Jaco (HTS teologiese studies, 2014)
The gift of discernment as mirror for the church. In the encounter between man and the Holy, man reacts with the ambivalent emotion of fear and fascination. Man is confronted by something incomprehensible. How will man know whether this is God? Any response by man, even faith, might be a self-deception. This condition is called ‘bad faith’ by Sartre and Berger. In an existential struggle with the numineuse, man constantly tries to get to know God and his will. This struggle is faith. The Holy Spirit bestows the gift of faith on mankind. The pneumatic moment is when congruency is established between on the one hand the human identity arrived at in Christ and, on the other hand, the existential expression of the response to the calling by God.